‘At Risk Mental State’: An Audit of Tier 3 Clinical Standards - Adisha Kapila; Megan Viegas; Jonathan Bradley (BJPsych Open)
Aims: The At-Risk Mental State (ARMS), an attenuated psychotic syndrome, represents a critical period of vulnerability for the development of psychosis. Early identification and evidence-based intervention are crucial to reducing distress, improving long-term outcomes and public health costs. There are clear recommendations stated by National Institute for Health and Care Excellence (NICE) for the optimal management of ARMS in children and young people including early identification, access to psychological therapy and care co-ordination. Baseline audit data collected from Tier 3 teams within South West London and St George’s NHS Mental Health Trust (SWLSTG) highlighted significant variation in clinicians’ confidence and knowledge about ARMS, notably its identification criteria and optimal management. This audit sought to enhance clinician expertise of “At Risk Mental State” (ARMS) within Tier 3 Child and Adolescent Mental Health Services (CAMHS).